2021
DOI: 10.1007/s10482-021-01547-1
|View full text |Cite
|
Sign up to set email alerts
|

Marine Group-II archaea dominate particle-attached as well as free-living archaeal assemblages in the surface waters of Kongsfjorden, Svalbard, Arctic Ocean

Abstract: Marine archaea are a significant component of the global oceanic ecosystems, including the polar oceans. However, only a few attempts have been made to study archaea in the high Arctic fjords. Given the importance of Archaea in carbon and nitrogen cycling, it is imperative to explore their diversity and community composition in the high Arctic fjords, such as Kongsfjorden (Svalbard). In the present study, we evaluated archaeal diversity and community composition in the size-fractionated microbial population, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 78 publications
(135 reference statements)
1
5
0
Order By: Relevance
“…Our data suggest clear functional differences in PA and FL prokaryotes associated with suspended and sinking POM. For instance, Proteobacteria ( Gammaproteobacteria ) MAGs and Bacteroidota unbinned contigs had the genomic potential to degrade polysaccharides produced by phytoplankton with specific CAZymes, which is in line with previous findings ( 68 ), while archaeal functional predictions suggest capacity to degrade proteins, secondary metabolites, and carbohydrates from POM, also in agreement with previous reports ( 69 ). Therefore, despite the phylogenetic similarities between our MAGs, there is evidence that prokaryotes exhibit diverse functional traits.…”
Section: Discussionsupporting
confidence: 92%
“…Our data suggest clear functional differences in PA and FL prokaryotes associated with suspended and sinking POM. For instance, Proteobacteria ( Gammaproteobacteria ) MAGs and Bacteroidota unbinned contigs had the genomic potential to degrade polysaccharides produced by phytoplankton with specific CAZymes, which is in line with previous findings ( 68 ), while archaeal functional predictions suggest capacity to degrade proteins, secondary metabolites, and carbohydrates from POM, also in agreement with previous reports ( 69 ). Therefore, despite the phylogenetic similarities between our MAGs, there is evidence that prokaryotes exhibit diverse functional traits.…”
Section: Discussionsupporting
confidence: 92%
“…This new phylum was recently proposed after a metagenomic-assembled genome (MAG) analysis of seawater samples collected from the coast of Sydney, Australia ( 65 ). Thermoplasmatota members constitute 76% of this type of taxon in surface seawater samples ( 66 ). However, Thermoplasmatota members have also been found in peatlands and included methanogenic archaea affecting atmospheric CH 4 emissions ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no studies have reported the presence of archaea in industrially produced vinegar, and only Wu et al (2017) reported by metagenomics “shotgun” sequencing that around 8% of a traditional cereal vinegar microbiota were identified as archaea. Nitrososphaeraceae has been recently found as a part of microbial communities of marine water surfaces and soils by metagenomics and metatranscriptomics ( Clark et al, 2021 ; Jain and Krishnan, 2021 ). These microorganisms obtain energy by oxidizing ammonia to nitrite aerobically, thereby fixing CO 2 , but growth depends on the addition of small amounts of organic acids ( Stieglmeier et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%